CMAB009 plus irinotecan versus irinotecan‐only as second‐line treatment after fluoropyrimidine and oxaliplatin failure in KRAS wild‐type metastatic colorectal cancer patients: promising findings from a prospective, open‐label, randomized, phase III trial. Issue 1 (24th May 2019) - Shi, Yuankai; Li, Jin; Xu, Jianming; Sun, Yan; Wang, Liwei; Cheng, Ying; Liu, Wei; Sun, Guoping; Chen, Yigui; Bai, Li; Zhang, Yiping; He, Xiaohui; et al.
Abstract: Background: The 5‐ fluorouracil/leucovorin plus oxaliplatin (FOLFOX) regimen is the standard first‐line treatment for metastatic colorectal cancer (mCRC), however, the optimal second‐line regimen for KRAS wild‐type mCRC patients is still investigational. In this study, we aimed to determine the clinical efficacy and safety of CMAB009 plus irinotecan compared to irinotecan‐only as a second‐line regimen for treating KRAS wild‐type mCRC patients. Methods: Patients with KRAS wild‐type mCRC who had previously failed to respond to FOLFOX treatment were randomly assigned in a 2:1 ratio, to receive CMAB009 plus irinotecan or irinotecan‐only. Patients receiving irinotecan‐only were permitted to switch to CMAB009 therapy on disease progression and were grouped as the sequential‐CMAB009 arm. The primary endpoints were overall response rate (ORR) and median progression‐free survival (PFS). The secondary endpoints were median overall survival (OS), disease control rate (DCR), clinical benefit rate (CBR), and duration of response (DOR). Results: The CMAB009 plus irinotecan arm demonstrated significantly improved ORR (33.2% vs. 12.8%; P < 0.001) and longer median PFS (169 days vs. 95 days; P < 0.001) as compared to the irinotecan‐only arm. Patients receiving CMAB009 plus irinotecan also demonstrated improved DCR (80.1% vs. 65.2%, P < 0.001), CBR (30.0% vs. 14.6%, P < 0.001), and DOR (210 days vs. 109 days; P < 0.001) as compared to irinotecan‐only. However, patients treated with CMAB009 had an increased risk of skin rash (66.9% vs. 5.5%, P < 0.001) and paronychia (9.8% vs. 0.0%, P < 0.001). Anti‐drug antibodies (ADA) were detected in 3.6% of patients, and only 0.9% of patients who received CMAB009 experienced hypersensitivity reactions. In patients receiving sequential‐CMAB009 therapy after failure with irinotecan, their median PFS was 84 days (95% CI 65 to 113 days). The median OS was 425 days for patients receiving CMAB009 plus irinotecan and 401 days for those with sequential‐CMAB009 ( P = 0.940). Conclusions: Treatment with CMAB009 plus irinotecan was found to be a superior second‐line regimen in comparison to irinotecan‐only in KRAS wild‐type mCRC patients. Further, switching to CMAB009 can be considered as an efficient third‐line of treatment after treatment failure with second‐line irinotecan‐only. Trial registration ClinicalTrials.gov : NCT01550055, retrospectively registered on March 9, 2012.